Εφαρμογή και συντονισμός δεικτών διασφάλισης ποιότητας για την μέτρηση της απόδοσης των διοικητικών υπηρεσιών του ΤΕΠΑΚ - Χριστοφή, Παναγιώτης (Τμήμα Μηχανολόγων Μηαχνικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Implementation and monitoring of Quality Assurance Indicators for Measuring the Performance of Administration Services of the C.U.T. Objective: The research is conducted in the Administration Services of the C.U.T. The aim is to investigate the effectiveness of Quality Assurance System (QAS) in Administration Services through the monitoring of Key Performance Indicators. In addition it aims to contribute to the QAS areas that need improvement and correction. Purpose: The purpose of the research is to investigate the most important Key Performance Indicators (KPI) applied in Administration Services of C.U.T, in order to check the effectiveness of those indicators concerning control services. The whole research and implementation is done in three Administration Services of C.U.T. which have been selected. For this research purposes the Library Service, the Service of Academic Affairs, the Student Affairs and the Service of Information Systems and Technology were selected. Methodology: In collaboration with the head of each service as well as with the person responsible for monitoring measurement indicators, the processes that had quality problems and needed improvement were identified. Based on this investigation the most important indicators of each service were selected. The next step was the collection of data concerning the selected indicators mentioned above, for a period of three months, in order to monitor and investigate the behavior of processes. Existing data from previous years were also used in most indicators. After being provided with the data by those responsible for monitoring the indicators, the researcher prepared the appropriate templates and input these data in Excel software. The researcher selected the appropriate type of control panel that should be used for each indicator. Then, using the software Statistical Process Control Spc-Excel the control panels of each indicator were prepared. For some indicators two different types of control panels were prepared for better monitoring, followed by a statistical analysis. Results: This research showed the effectiveness of the Quality Assurance System implemented in Administration Services in controlling their procedures. Moreover, the benefits deriving from the QAS application to the C.U.T Administrative Services were obvious. The research also shows the necessity for using indicators to control the services procedures in order to measure the results and monitor the objectives. Throughout the statistical analysis, the need for improvement and for better supply as well as customers service was indicated regarding the processes of the three selected services. It is acknowledged that the whole quality system and performance indicators are premature with very small amount of data collected, therefore the benefits of these statistics as a future reference are not that obvious for the time being. That is why there were only few points out of control and specification limits, since no standards or limits have been set. These will be determined by the working groups of each service, after monitoring the vi indicators for a period of time in order to find the range and distribution of measurements. This is in alignment with one of the 14 points of the quality guru E.W. Deming ¨ Avoid setting arbitrary Goals ¨. There will be many benefits arising from a full implementation of quality assurance system and from monitoring the indicators. The benefits will apply not only to the well- functioning of the university but also to the improvement of the quality of supply and customer services.
Keywords: Quality Assurance System; Administration Services; Σύστημα διασφάλισης ποιότητας; Διοικητικές υπηρεσίες